A proof-of-concept randomised controlled trial of an intervention designed to improve food hygiene behaviours among caregivers of young children living in low-income areas of Nairobi, Kenya - Watson, J.; Okumu, Noah O.; Wasonga, Joseph O.; Majiwa, Hamilton; Kiarie, Alice; Masudi, Sherril P.; Ochieng, Linnet; Alumasa, Lorren; Mutisya, Christine; Cook, Elizabeth A.J.; Cumming, O. (2024)
Young children are particularly vulnerable to foodborne disease due to their immature immune systems. Safe food hygiene behaviours by caregivers can potentially reduce this disease burden. Here, we evaluate the potential for a locally designed intervention to improve caregivers’ food hygiene behaviour in a peri-urban, low-income area of Nairobi, Kenya. In this cluster-randomised proof-of-concept trial, 50 community health volunteers (CHVs) were randomly assigned to intervention or control arm (1:1). 101 households under the CHV’s catchment (2-3/CHV), with at least one child aged 6–24 months, participated. Caregivers in intervention households (n = 50) received the CHV-delivered food hygiene intervention. The control arm (n-51) received no intervention. Blinding was not possible due to the nature of the intervention. Our primary outcome was the proportion of caregivers observed to practice all five pre-specified food hygiene behaviours, four weeks post intervention delivery. Secondary outcomes assessed the five observed behaviours individually plus a sixth behaviour—the proportion of caregivers who report always boiling the child’s drinking water. We found no between-arm difference in the proportion of caregivers practising all five observed behaviours. However individually, five behaviours were significantly improved. Specifically, caregivers in the intervention arm had higher odds of washing their hands before feeding the child (adjusted odds ratio (aOR) = 7.40, 95%CI 1.85, 29.62) and before preparing the child’s food (aOR = 7.05, 95%CI 1.52, 32.71), washing the child’s hands before eating (aOR = 21.57, 95%CI 1.15, 405.93) and heating the child’s food (aOR = 4.03, 95%CI 1.27, 12.85) and drinking water (aOR = 12.82, 95%CI 2.54, 64.77) to boiling. There was no effect on cleaning and storage of feeding utensils. This study offers promising preliminary evidence that a CHV-led intervention targeting caregivers of young children can improve their food hygiene behaviour. Our findings warrant further research to refine the intervention and undertake larger scale trials to explore the intervention’s potential impact more comprehensively.